2001
DOI: 10.1162/10636560152642850
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coating Designs Using the Family Competition Evolutionary Algorithm

Abstract: A robust evolutionary approach, called the Family Competition Evolutionary Algorithm (FCEA), is described for the synthesis of optical thin-film designs. Based on family competition and adaptive rules, the proposed approach consists of global and local strategies by integrating decreasing mutations and self-adaptive mutations. The method is applied to three different optical coating designs with complex spectral quantities. Numerical results indicate that the proposed approach performs very robustly and is ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The results of the authors' earlier work have demonstrated that these mechanisms are effective in solving continuous optimization problems in some fields [29]- [31]. The main difference in methodology between the present work and our previous studies is the addition of two problem-specific operators for efficiently optimizing the clustering and ordering of genes.…”
Section: Introductionmentioning
confidence: 80%
“…The results of the authors' earlier work have demonstrated that these mechanisms are effective in solving continuous optimization problems in some fields [29]- [31]. The main difference in methodology between the present work and our previous studies is the addition of two problem-specific operators for efficiently optimizing the clustering and ordering of genes.…”
Section: Introductionmentioning
confidence: 80%
“…So far, a great deal of effort has already been expended to precipitate the maturity of both the GA and the computational electromagnetic, as well as combining these two different techniques to perform rapid optimization of practical electromagnetic designs. Although the GA has been increasingly used in providing optimal or nearly optimal solutions to a number of optimization problems, the algorithm still has a certain probability of being trapped in a local optimum [20,21], albeit this probability is smaller than that in the traditional optimization methods. Therefore, a number of studies aiming to improve the algorithm's search ability have been done on the adaptive search rules and the fundamental theory of the GA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a number of studies aiming to improve the algorithm's search ability have been done on the adaptive search rules and the fundamental theory of the GA. Very recently, the family competition principle has been introduced [18,20,21] to the GA with the intent of improving the quality of the solution and increasing the probability of locating the global optimum. In the FCGA, the family competition can be seen as the local competition of each specific area of the search space (local search) and the selection in the reproduction process can be seen as the global competition in the universal tournament.…”
Section: Introductionmentioning
confidence: 99%
“…Our program used a simplified scoring function and a new evolutionary approach which is more robust than standard evolutionary approaches [14,15,16] on some specific domains [17,18,19,20]. Our energy function consisted only of steric and hydrogen-bonding terms with a linear model which was simple and fast enough to recognize potential complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to balance exploration and exploitation, the core idea of our evolutionary approach is to design multiple operators cooperating with each other by using the family competition which is similar to a local search procedure. We have successfully applied a similar idea to solve optimization problems in some differing fields [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%